CASE REPORTSSternal Talon, a novel repair for sternal dehiscence - Subramaniam, Thavakumar; Keita, Luther; Veerasingam, Dave (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
A 72-year-old man presenting with collapse and ventricular tachycardia was investigated for a possible acute cardiac event 2 years after coronary artery bypass grafting for ischemic heart disease. Work-up chest X-ray showed displacement of all sternal wires, and computed tomography (CT) performed to investigate further showed sternal dehiscence with right ventricle wall herniation through the defect and sternal wire breakdown. A decision was made after discussion with the patient to repair the defect using 3 Sternal Talon devices and 2 sternal wires. The patient made an uncomplicated recovery, and the outpatient clinic review after discharge home showed satisfactory and stable sternal union. We report a case of non-infected sternal dehiscence managed successfully with the Sternal Talon without long-term complications.